Political Communication Strategy of The Eramas Success Team's in Achieving Support at the 2018 Simular Election In North Sumatra - Muhammad Husni Ritonga; Anang Anas Azhar; Halim Perdana Kusuma (INJECT (Interdisciplinary Journal of Communication), 2021)
This research aims to find out: first the communication strategy of the ERAMAS success team in gaining support for the 2018 simultaneous regional elections in North Sumatra, the second the campaign communication strategy for the ERAMAS pair in attracting public attention, the three obstacles faced by the ERAMAS success team in the 2018 simultaneous regional elections in North Sumatra. This study uses qualitative research with a naturalistic approach, this approach intends to create a systematic and objective description of an event by collecting, evaluating, verifying, and synthesizing evidence to support facts in order to obtain a conclusion. Data collection in this study was carried out using various observation techniques (observations), interviews, and documentation. This research refers to the Scored theory which states that political communication strategy is divided into political marketing, political campaigns, media and political jargon. The results show that: first, the communication strategy of the ERAMAS success team in gaining support for the 2018 simultaneous regional elections in North Sumatra is by: a) direct alternation, b) involving all elements of society, and c) maximizing the role of social media. Two Communication Strategies The campaign for the ERAMAS pair in attracting public attention is by: a) dialogical and open, b) campaigning culturally and structurally, and c) holding religious and social activities. The three obstacles faced by the ERAMAS success team in the 2018 simultaneous regional elections in North Sumatra are: a) remote geographical location, b) lots of slander and bad framing, and c) intervention from the central government. Meanwhile, the solutions taken to overcome these obstacles are: a) forming a solid team, b) continuing to campaign politely and obeying the rules, and c) convincing the community by providing the best vision and mission